2004
DOI: 10.1007/bf02298830
|View full text |Cite
|
Sign up to set email alerts
|

Wage inequality and firm performance: Professional basketball's natural experiment

Abstract: The purpose of this inquiry is to utilize a natural experiment from professional basketball to examine how wage inequality impacts the productivity of the firm. The A Natural Experiment from Professional BasketballAn issue highlighted in the National Basketball Association's (NBA) 1998-99 labor strife was the disappearance of the league's middle class. While a few athletes had garnered the attention of the media for contracts in excess of 100 million dollars, a larger number of veteran players were playing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 24 publications
2
39
0
Order By: Relevance
“…For this purpose, we need a conditional measure of pay inequality that controls for the quality of a worker's 1 In an interesting variation on this literature, Katayama and Nuch (forthcoming) model the impact of salary dispersion on team performance in the NBA at game level. They find, in line with Berri and Jewell (2004), no effect of within-team pay disparity on team performance, using estimation methods similar to this paper. teammates (Winter-Ebmer and Zweimüller, 1999;Lallemand et al, 2004).…”
Section: Team Performance and Pay Inequality In The Nbasupporting
confidence: 85%
“…For this purpose, we need a conditional measure of pay inequality that controls for the quality of a worker's 1 In an interesting variation on this literature, Katayama and Nuch (forthcoming) model the impact of salary dispersion on team performance in the NBA at game level. They find, in line with Berri and Jewell (2004), no effect of within-team pay disparity on team performance, using estimation methods similar to this paper. teammates (Winter-Ebmer and Zweimüller, 1999;Lallemand et al, 2004).…”
Section: Team Performance and Pay Inequality In The Nbasupporting
confidence: 85%
“…A substantial empirical literature has established a positive correlation between spending on team payrolls and team performances in European soccer and major North American sports (Szymanski and Smith, 1997;Szymanski and Kuypers, 1999;Szymanski, 2000;Hall et al, 2002;Berri and Jewell, 2004;Simmons and Forrest, 2004;Kahane, 2005). The motivation for this relationship is that player quality is easily observed and players are easily traded, at least in European soccer.…”
Section: Introductionmentioning
confidence: 90%
“…The authors concluded that franchise owners may increase dispersion by acquiring high-salaried star players in order to sell season tickets, premium seating, and luxury boxes, perhaps at the expense of winning percentage. Berri & Jewell (2004) and Katayama & Nuch (2011) examined pay dispersion through performance relationships among teams in the US National Basketball Association (NBA). Both studies found that the relationship between inequality measures and team performance was negative, but not significantly so.…”
Section: Team Performancementioning
confidence: 99%